A lateral organ boundaries domain transcription factor acts downstream of the auxin response factor 2 to control nodulation and root architecture in Medicago truncatula - Kirolinko, Cristina Alejandra (2024)
Legume plants develop two types of root postembryonic organs, lateral roots and symbiotic nodules, using shared regulatory components. The module composed by the microRNA390, the Trans-Acting SIRNA3 (TAS3) RNA and the Auxin Response Factors (ARF)2, ARF3, and ARF4 (miR390/TAS3/ARFs) mediates the control of both lateral roots and symbiotic nodules in legumes.Here, a transcriptomic approach identified a member of the Lateral Organ Boundaries Domain (LBD) family of transcription factors in Medicago truncatula, designated MtLBD17/29a, which is regulated by the miR390/TAS3/ARFs module. ChIP-PCR experiments evidenced that MtARF2 binds to an Auxin Response Element present in the MtLBD17/29a promoter. MtLBD17/29a is expressed in root meristems, lateral root primordia, and noninfected cells of symbiotic nodules.Knockdown of MtLBD17/29a reduced the length of primary and lateral roots and enhanced lateral root formation, whereas overexpression of MtLBD17/29a produced the opposite phenotype. Interestingly, both knockdown and overexpression of MtLBD17/29a reduced nodule number and infection events and impaired the induction of the symbiotic genes Nodulation Signaling Pathway (NSP) 1 and 2.Our results demonstrate that MtLBD17/29a is regulated by the miR390/TAS3/ARFs module and a direct target of MtARF2, revealing a new lateral root regulatory hub recruited by legumes to act in the root nodule symbiotic program.